The influence of the municipal human development index and maternal education on infant mortality: an investigation in a retrospective cohort study in the extreme south of Brazil - Carolina Ribeiro Anele; Vânia Naomi Hirakata; Marcelo Zubaran Goldani; Clécio Homrich da Silva (BMC, 2021)
Abstract Background Infant mortality is considered an important and sensitive health indicator in several countries, especially in underdeveloped and developing countries. Most of the factors influencing infant mortality are interrelated and are the result of social issues. Therefore, this study performed an investigation of the influence of the MHDI and maternal education on infant mortality in a capital in the extreme south of Brazil. Methods It is a retrospective cohort study with data on births and deaths in the first year of life for the period of 2000-2017. The association between the independent variables and the outcome was done by bivariate analysis through simple Poisson regression. The variables that can potentially be considered confounding factors were used in a multiple Poisson regression for robust variances - adjusted model. Results The study included 317,545 children, of whom 3107 died. The medium MHDI showed associated with infant death in the first year of life. Maternal education, individually and jointly analyzed with the MHDI, showed association with the outcome of infant death in the first year of life, particularly for children of mothers with lower maternal education (p < 0.001). In relation to other related factors, maternal age; number of Prenatal Care Consultations; gestational age, weight, gender and Apgar Index (5th minute) of the newborn showed association with IM (p < 0.001). Conclusions The HDI is considered a good predictor of infant mortality by some authors and the analyzes of the present study also confirm an association of the medium MHDI and its low MHDIE component with infant mortality. In addition, it was maternal education with less than 8 years of study that that demonstrated a higher risk of death, revealing itself to be a social determinant with a relevant impact on infant mortality. Thus, it is possible to conclude that maternal education is available information, and it is superior to the MHDI to assess the infant mortality outcome.